Lisbon´s Real Estate Analysis based on Proximity Calculations - Valério, Maria Madalena Jorge do Nascimento (2023)
Project Work presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Business Analytics